Grelina potencia a taquicardia evocada por estresse emocional agudo - Silva , Gabriel Camargo da (2016)
Ghrelin is a 28 amino acid peptide described at 90’s. Within its multiple functions, production of growth hormone (GH), food intake, cell proliferation, regulation of cardiovascular system and behavior may be highlighted. Ghrelin actions are mediated by the growth hormone secretagogue receptor subtype 1a (GHS-R1a), which is distributed along several peripheral tissues and central areas involved in the control of cardiovascular responses to aversion. Since GHS-Rs1a is expressed in central areas that govern cardiovascular responses to aversion, our aim was to assess the role of Ghrelin in the cardiovascular reactivity to acute emotional stress. Adult male Wistar rats (250-350g) underwent acute emotional stress following i.v. injection of ghrelin (1 or 10 µg/kg), the antagonist of GHS-R1a (PF04628935) or vehicle (VHE). We further investigated the cardiac beta-adrenergic sensitivity in vivo by injecting isoproterenol (1 µg/kg) and ghrelin (10 µg/kg). Autonomic blockade was reached by subsequent injections of atenolol (4 mg/kg), methylatropine (3 mg/kg), ghrelin (10 µg/kg) e VHE. Finally, we evaluated in isolated hearts the effects of perfusion with ghrelin (0.2nMol/L) followed by crescent bolus concentrations of isoproterenol and acetylcholine. Current findings show that ghrelin potentiates the tachycardia evoked by restraint and by air jet stress. We demonstrated that administration of ghrelin improves beta-adrenergic sensitivity in vivo and ex vivo. Autonomic blockade experiments revealed that autonomic nervous system, through sympathetic branch, modulates the stress-evoked positive chronotropy. Furthermore, perfusion of isolated hearts with ghrelin resulted in positive inotropy and potentiated contractile responses caused beta-adrenergic agonism, without altering the amplitude of the responses evoked by acetylcholine. In conclusion, administration of ghrelin and the consequent activation of GHS-R1a increased the magnitude of the tachycardia evoked by acute emotional stress by modulating autonomic nervous system and through peripheral mechanisms, strongly dependent on activation of cardiac beta-adrenergic receptors.